Penerapan Inovasi Layanan Dalam Mempengaruhi Kepuasan Pelanggan Guna Meningkatkan Loyalitas Nasabah - Hamidin, Fachrul; Iriani, Nisma; Taaha, Yulian Rinawaty; Julian, Sanny Feria; Putera, Wahyudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The study uses a direct and indirect influence approach direct and indirect effects using the path analysis method (independent variables, intermediate variables and dependent variables). In this study, variable X is service innovation, variable Y is customer satisfaction and variable Z is customer loyalty. Technique data collection technique with simple random sampling method, namely sampling from the existing population randomly with a sample size of 40 customers / customers through questionnaires and documentation. Data analysis techniques with descriptive statistical analysis and path analysis using the SPSS Ver,-2024 program through questionnaire information collection in the form of questions and statements. Indirect test results shows that service innovation variables have a significant effect on customer satisfaction at PT. Jeneponto Branch Pawnshop with service innovation provided to customers provided to customers, the customers are very well served with the existence of innovative and creative services, flexible service options and different service concepts. Furthermore, directly the effect of service innovation service innovation has a significant effect on customer loyalty at PT. Pengadaian Cabang Jeneponto because with the service innovation that is implemented there are several things especially in the flexible and different services provided then the customers appreciate so much that customer loyalty increases. As well as directly or indirectly showing that the customer satisfaction variable has a significant effect on customer loyalty at PT Jeneponto Branch Pawnshop with the achievement of service innovation, customer satisfaction is fulfilled with customers / customers feeling happy with the services provided, the services provided are as expected, getting easy access to services and past experiences felt in using services that directly increase customer loyalty with customers / customers making regular purchases or repeat purchases, buying between product lines, recommending products to others and showing immunity from the attractiveness of similar products. Thus the customer satisfaction variable has a dominant influence in increasing customer loyalty at PT Jeneponto Branch Pawnshop.